Study of Complex Landscape Gully Erosion and Theirs, Density and Density Mapping (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Mapping of ravine erosion in complex landscape conditions in the world practice of erosion management, linear forms of ravine erosion are usually mapped by deciphering aero-space-photographs (AFS-CFS), as well as traditional mapping methods - using topographic maps. The article provides for the regularities in the manifestation of the growth and development of the ravines of the Namangan adyrs, studied the linear forms of erosion with the identification of their morphological and morphometric characteristics.